The risk management and audit function at State Religious Council in Malaysia / Nur Faratul Anati Abdul Halim Sabir - Abdul Halim Sabir, Nur Faratul Anati (Academy of Contemporary Islamic Studies (ACIS), 2018)
In general, the administration of state Islamic religious affair in Malaysia is divided by three which is the State Religious Council (SRC), Mufti and the Shariah Court. These state administrations need a proper management to achieve their organisations objectives. Thus, this study is focuses on the importance of risk management function at State Religious Council (SRC) in Malaysia. The aims of this study is to explore the risk management function in public sector, analyse the function of State Religious Council (SRC) in Malaysia and to find out the existing of risk management and audit function in State Religious Council (SRC) in Malaysia. This is due to the management of the SRC todays are exposed to the issues and usually get negative perspective from society. One of the common problems that face by SRC is the weak management of waqf land, the poor zakat system management including the imbalance between the amount quoted and the amount distributed to the asnaf and failure and delay in the distribution of the estate. As for this, SRC need to improve in administration and management. Highly recommend the SRC to forms risk management function at SRC as well as improve the audit function that existed. Hence, this study objectives will achieve through content analysis method.